2005
DOI: 10.1111/j.1099-1123.2005.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit Fees and the Large Auditor Premium in the Italian Market

Abstract: The objective of this research is to highlight the determinants of audit fees in the Italian audit market. As described later, Italy is not directly comparable with other countries where these kinds of studies have been conducted. Furthermore, the Big Italian audit firms were condemned by the Italian Antitrust Authority for price fixing in 2000. A fee model for the Italian market is developed. Consistent with previous studies, findings show that the size, the complexity of auditee, and audit risk have an impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 38 publications
3
41
0
12
Order By: Relevance
“…Companies with complexity require more time and effort than smaller companies, and in turn pay higher fees. The current findings are consistent with the most research done on audit fees determinants (Sandra & Patrick, 1996;Joshi & Al-Bastaki, 2000;Simon & Tylor, 2002;Cameran, 2005;Al-Harshani, 2008;El-Gammal, 2012;Soyemiand & Olowookere, 2013). They found a positive relationship between audit fees and company size and complexity.…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 91%
See 1 more Smart Citation
“…Companies with complexity require more time and effort than smaller companies, and in turn pay higher fees. The current findings are consistent with the most research done on audit fees determinants (Sandra & Patrick, 1996;Joshi & Al-Bastaki, 2000;Simon & Tylor, 2002;Cameran, 2005;Al-Harshani, 2008;El-Gammal, 2012;Soyemiand & Olowookere, 2013). They found a positive relationship between audit fees and company size and complexity.…”
Section: Wwwccsenetorg/ijbmsupporting
confidence: 91%
“…Consistent with prior studies (Langendijk, 1997;Cameran, 2005;Gonthier & Schatt, 2006;Thinggaard & Kiertzner, 2008;El-Gammal, 2012;Hassan & Naser, 2013, Soyemi & Olowookere, 2013, a questionnaire was developed to explore the determinants of audit fees. It consists of two parts: Part 1 consists of questions asking the participants about their filed work; Part 2 contains 25 questions focusing on the factors that determine the audit fees.…”
Section: The Questionnairementioning
confidence: 99%
“…The Emirati companies listed on the exchange are divided into 30 financial companies (14 banks and 16 insurance companies) and 30 nonfinancial. Drawing from previous studies on audit fees, financial companies are excluded from the current study since these companies have special nature of activities and they have different fees structure than the nonfinancial companies (Basioudis & Fifi, 2004;Cameran, 2005;Simunic, 1980). Thus, the 2011 annual reports together with the governance reports for all companies listed on ADX were covered in the current study.…”
Section: Data Collection and Methodologymentioning
confidence: 99%
“…Companies with several subsidiaries are considered to be more complex than companies with few or without subsidiaries. A significant proportion of previous studies observed positive relationship between corporate complexity and audit fees (Simunic, 1980;Brinn et al, 1994;Cameran, 2005;Joshi & Bastaki, 2000;Clatworthy & Peel, 2006;Thinggaard & Kiertzner, 2008;Vermeer et al, 2009;Ellis & Booker, 2011;Verbruggen et al, 2011). The main reasons advanced in the literature to explain such a relationship is that greater number of subordinate financial statements require more audit time and greater expertise to ensure the accuracy of the consolidated financial statements (Sandra & Patrick, 1996).…”
Section: Complexitymentioning
confidence: 96%
“…Firms with financial problems have greater incentives to manipulate earnings (DeFond and Jiambalvo, 1994). Financial distress may further be related to higher audit risk and increased audit procedures (Cameran, 2005). In this context, a variable stating the proportion of own equity, SOLVENCY, and a performance variable, ROA, have been included in the regression models.…”
Section: Control Variablesmentioning
confidence: 99%